2018
DOI: 10.5194/acp-18-4981-2018
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations and source regions of light-absorbing particles in snow/ice in northern Pakistan and their impact on snow albedo

Abstract: Abstract. Black carbon (BC), water-insoluble organic carbon (OC), and mineral dust are important particles in snow and ice which significantly reduce albedo and accelerate melting. Surface snow and ice samples were collected from the Karakoram-Himalayan region of northern Pakistan during 2015 and 2016 in summer (six glaciers), autumn (two glaciers), and winter (six mountain valleys). The average BC concentration overall was 2130 ± 1560 ng g −1 in summer samples, 2883 ± 3439 ng g −1 in autumn samples, and 992 ±… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 78 publications
0
23
0
Order By: Relevance
“…The WRF-STEM CO tracer and HYSPLIT model classify different geographical regions affecting the air quality over Dibrugarh. The WRF-STEM model used in the present study has already been validated over the complex terrain in Central and Western Himalayan region [75,76]. In contrast to WRF-Chem and WRF-STEM, HYSPLIT is a computationally inexpensive and easily accessible model for identification of concentration pathways.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The WRF-STEM CO tracer and HYSPLIT model classify different geographical regions affecting the air quality over Dibrugarh. The WRF-STEM model used in the present study has already been validated over the complex terrain in Central and Western Himalayan region [75,76]. In contrast to WRF-Chem and WRF-STEM, HYSPLIT is a computationally inexpensive and easily accessible model for identification of concentration pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Under low RH condition, the significant impact of regional transportation, local emissions, and physicochemical formation jointly dominates the concentration of atmospheric particles [81]. Thus, an increase in the value of RH is favorable for the formation of particles from the liquid-phase, heterogeneous reactions and the hygroscopic growth processes [75]. High T, low wind and RH play a significant role in the enrichment of regional pollution.…”
Section: Evaluation Of Surface Meteorologymentioning
confidence: 99%
“…In Pakistan, 3 stations (namely Karachi, Mardan, and Hunza) were studied based on the APCC program (Gul et al, 2018).…”
Section: Stations For the Aerosol And Precipitation Studiesmentioning
confidence: 99%
“…South-eastern Tibet receives biomass-burning emissions from Myanmar, Bangladesh, and eastern India (Zhao et al 2013), while the northern parts of the Tibetan Plateau receive dust from the Taklimakan Desert (Huang et al 2007;Cao et al 2009;Xiao et al 2010;Chen et al 2013;Zhao et al 2013;Wang et al 2015). Pollution episodes at Mount Waliguang at the north-eastern corner of the HKH, as well as at Mount Muztagh Ata, in the Pamir range and in the Pakistani Karakoram, have been traced to Central Asia and the Middle East (Wang et al 2006;Che et al 2011;Gul et al 2018). Manora Peak in India receives pollution from the IGP, but also from the Middle East (Dumka et al 2010(Dumka et al , 2015.…”
Section: Source Regions and Transport Pathways For Pollution Reachingmentioning
confidence: 99%
“…However, the model does give an overall synoptic picture, consistent with the expected behaviour of pollution transport reaching the high glaciers of the HKH. Several research papers using wind back trajectories analysis report that the source of the observed air pollutants reaching the HKH are primarily from the IGP and as far away as Africa (Carrico et al 2003;Bonasoni et al 2012;Ming et al 2009;Babu et al 2011b;Lu et al 2012;Gul et al 2018).…”
Section: Source Regions and Transport Pathways For Pollution Reachingmentioning
confidence: 99%